Conservation of the relative tRNA composition in healthy and cancerous tissues - Mahlab, Shelly (Cold Spring Harbor Laboratory Press, 2012)
Elongation in protein translation is strongly dependent on the availability of mature transfer RNAs (tRNAs). The relative concentrations of the tRNA isoacceptors determine the translation efficiency in unicellular organisms. However, the degree of correspondence of codons and the relevant tRNA isoacceptors serves as an estimator for translation efficiency in all organisms. In this study, we focus on the translational capacity of the human proteome. We show that the correspondence between the codon usage and tRNAs can be improved by combining experimental measurements with the genomic copy number of isoacceptor groups. We show that there are technologies of tRNA measurements that are useful for our analysis. However, fragments of tRNAs do not agree with translational capacity. It was shown that there is a significant increase in the absolute levels of tRNA genes in cancerous cells in comparison to healthy cells. However, we find that the relative composition of tRNA isoacceptors in healthy, cancerous, or transformed cells remains almost identical. This result may indicate that maintaining the relative tRNA composition in cancerous cells is advantageous via its stabilizing of the effectiveness of translation.